Study of safety parameters of meat pates - Moskaluyk, Oksana; Hashchuk, Oleksandra; Peshuk, Ludmila; Lytvynenko, Daria (My University, 2018)
In order to determine the influence of the proposed plant components on the expiration of meat pastes, bacteriological studies were carried out, namely, the number of mesophilic aerobic and facultative-enaerobic microorganisms (MAFEiM), bacteria of the coliform stem (BGKP), sulfitreducing clostridia, pathogenic flora, in that including bacteria of the genus Salmonellae, which characterize the safety of meat pastes for consumption. Для визначення впливу запропонованих компонентів рослини на витримку м'ясних паст були проведені бактеріологічні дослідження, а саме кількість мезофільних аеробних та факультативно-енаеробних мікроорганізмів (MAFEiM), бактерій стовбура коліфоруму (BGKP), сульфіторедукції клостридії, патогенна флора, у тому числі бактерії роду Salmonellae, які характеризують безпеку м'ясних паст для споживання.
Keywords: паштет; paste; паста; paste; мікроорганізми; microorganisms; кафедра технології м’яса і м’ясних продуктів